Prinsip Pemanfaatan Ruang Angkasa berdasarkam The OST 1967 dan Impelemntasinya terhadap Kasus Penggunaan Anti Satelit oleh India - Rizki Dwi Widyadhi; Neni Ruhaeni (Bandung Conference Series: Law Studies, 2024)
In principle, the use of outer space is free and open to all countries in the world without discrimination in accordance with Article 1 of the Outer Space Treaty 1967. According to Bin Cheng, space law is a series of international legal regulations that regulate the exploration and exploitation of outer space. including the moon and the celestial bodies in it. The Outer Space Treaty is an international agreement which aims to regulate rights and obligations, as well as prohibitions and permits in the exploration and exploitation of outer space and the celestial bodies in it. All types of activities are permitted as long as they are carried out for peaceful purposes. Use of outer space for military purposes is not permitted as regulated in Article 4 of the Outer Space Treaty. India's testing of the PDV-MK II anti-satellite ballistic missile by the Defense Research and Development Organization (DRDO) was deemed to have violated the provisions of the Articles of the Outer Space Treaty 1967. The formulation of the problem in this research is as follows: "How is space utilization regulated based on The Outer Space Treaty against anti-satellite testing carried out by India?” and “How does the Outer Space Treaty regulate anti-satellite ballistic missile testing carried out by India?”. Researchers use normative juridical methods, namely legal research carried out by examining The Outer Space Treaty as a legal norm. The data collection technique used in this research is literature study. The data analysis technique used in this research is qualitative analysis technique. The results of this research are that India violated the provisions of Article 4 of the Outer Space Treaty regarding the demilitarization of outer space Pemanfaatan Ruang angkasa pada prinsip dasarnya bersiat bebas dan terbuka bagi seluruh negara di dunia tanpa adanya diskriminasi sesuai dengan yang tercantum dalam Pasal 1 The Outer Space Treaty 1967. Menurut Bin Cheng, hukum ruang angkasa adalah serangkaian peraturan hukum internasional yang mengatur eksplorasi dan eksploitasi ruang angkasa termasuk bulan dan benda-benda langit di dalamnya. The Outer Space Treaty merupakan perjanjian internasional yang bertujuan untuk mengatur hak dan kewajiban, serta larangan dan kebolehan dalam eksplorasi dan eksploitasi ruang angkasa besrta benda langit di dalamnya. Segala jenis kegiatan diperbolehkan selama dilakukan dengan tujuan damai. Pemanaatan Ruang angkasa demi kepentingan militer tidak diperbolehkan sebagaimana yang diatur dalam Pasal 4 The Outer Space Treaty. India melakukan pengujian misil balistik anti-satelit PDV-MK II oleh Defence Research and Development Organisation(DRDO) dinilai telah melanggar ketentuan dari Pasal-Pasal The Outer Space Treaty 1967. Perumusan masalah dalam penelitian ini sebagai berikut: “Bagaimana pengaturan pemanfaatan ruang angkasa berdasarkan The Outer Space Treaty terhadap pengujian anti-satelit yang dilakukan oleh India?” dan “Bagaimana The Outer Space Treaty mengatur tentang pengujian misil balistik anti satelit yang dilakukan oleh India?”. Peneliti menggunakan metode yuridis normatif yaitu penelitian hukum yang dilakukan dengan cara mengkaji The Outer Space Treaty sebagai norma hukum. Dengan teknik pengumpulan data yang digunakan dalam penelitian ini adalah studi pustaka. Adapun teknik analisis data yang digunakan dalam penelitian ini adalah teknis analisis kualitatif. Hasil penelitian ini adalah India menyalahi ketentuan Pasal 4 The Outer Space Treaty tentang demiliterisasi ruang angkasa.